Entangled Interactions between Religions and National Identities in the Eastern Borderland of Europe - Aoshima, Yoko (Lithuanian studies without Borders, 2020)
"This book elucidates the complicated relationship between religion and national consciousness in the modern world, highlighting various cases in Central and Eastern Europe. Though those analyses, the authors show how religion, far from disappearing, strongly impacted the emerging national consciousness. Starting with the pre-modern era in this region, the book examines the long-term transformation of religious, political, and social situations of the region. In addition, the book considers the impact of imperial powers, which tended to be linked with a universal religion. It finally sheds light on the multifaceted nature of nations in this region, which contributes to evoke a new vision of the historical transformation of the region that enriches the general theories of nationalism"--